Pengaruh Pengalaman Pelanggan dan Kualitas Layanan Elektronik Terhadap Kepuasan Pelanggan Layanan Pesan Antar Makanan Gofood di Surabaya - Boby Yudho Anggoro; Rizky Dermawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
service to its consumers. The emergence of many competitors has pressured Gofood to find effective strategies to become the market leader. The purpose of this study is to determine the influence of customer experience and electronic service quality on customer satisfaction with Gofood’s food delivery service in Surabaya. This research employs a quantitative method. The population in this research consist of the residents of Surabaya. The targeted sample includes residents of Surabaya who have utilized and purchased Gofood as a food delivery service with 98 respondents. The sampling process uses a non-probability sampling method through purposive sampling techniques. The results of this research reveal: 1) customer experience has a positive and significant effect on customer satisfaction and 2) electronic service quality has a positive and significant effect on customer satisfaction.